Prūsistika K. O. Falko rankraštiniame palikime - Stundžia, Bonifacas (Baltistica, 1996)
PRUSSIAN PHILOLOGY IN K. O. FALK’S MANUSCRIPTSOn the basis of the preliminary analysis of Knut Olof Falk’s (1906–1990) manuscripts the conclusion can be drawn that the research into the Germanization of Prussian proper names, toponyms and vocabulary is Falk’s main merit to Old Prussian philology. Deserving attention is the idea about the substitutional and additional final -e as an inflectional element of Middle Low German, with the help of which Germans used to grammaticalize proper names and sometimes appellatives of Old Prussian. An attempt to interpret toponyms in -ayn, -ayen, -igen, etc. as having the authentic non-suffixal pluralia tamtum form in -(i)ai seems to be less convincing.
Keywords: prūsų kalba; prūsistika